Letting $\theta: \mathbb{R}^n\times\mathbb{R}^m \to \mathbb{R}$, we say $\theta(x;q)$ satisfies the single crossing property if , for all $x,y\in\mathbb{R}^n$ and $q,r\in\mathbb{R}^m$ such that $x\geq y$ and $q\geq r$:

$$ \theta(x;r) \geq \theta(y;r) \to \theta(x;q) \geq \theta(y;q) $$


$$ \theta(x;r) > \theta(y;r) \to \theta(x;q) > \theta(y;q). $$

If $\theta$ is twice-differentiable with $\frac{\partial \theta}{\partial x_i \partial q_k}>0$ for all $i$ and $k$, then $\theta$ satisfies the single crossing property.

I am not quite sure about this, my first attempt would make use of the definition of second derivative assuming dimension of $x$ and $q$ are both one.

$$ \frac{\partial^2 \theta}{\partial x \partial q} = \lim_{h\to 0}\lim_{\Delta \to 0} \frac{\theta(x+h,q+\Delta)-\theta(x,q+\Delta)-\theta(x+h,q)+\theta(x,q)}{\Delta h} $$

If as we reach the limit the sign is maintained

$$ \theta(x+h,q+\Delta)-\theta(x,q+\Delta) >\theta(x+h,q)-\theta(x,q) >0 $$ with the last step following from dimensions being one.


1 Answer 1


Actually given the sign on the cross partial derivatives, the stronger inequality $$ \theta(x;q) - \theta(y;q) \ge \theta(x;r) - \theta(y;r), $$ holds for all $x \ge y$ and $q \ge r$.

To see this, one can use the multivariate mean value theorem (assuming that $\theta$ is $C^2$).

First we have that there exists some $s$ for which $r \le s \le q$ and: $$ \left(\theta(x;q) - \theta(y;q)\right) - \left(\theta(x;r) - \theta(y;r)\right) = \sum_i \left[\frac{\partial \theta(x;s)}{\partial q_i} - \frac{\partial \theta(y;s)}{\partial q_i}\right](q_i - r_i). $$

For the term between square brackets, we can once more apply the multivariate mean value theorem: For all $i$, there exists a $z^i$ such that $y \le z^i \le x$ and (I index $z^i$ by $i$ as the value of the vector might be different for different $j$): $$ \frac{\partial \theta(x;s)}{\partial q_i} - \frac{\partial \theta(y;s)}{\partial q_i} = \sum_j \frac{\partial^2 \theta(z^i;s)}{\partial q_i \partial x_j}(x_j - y_j) $$

Putting the two together gives: $$ \left(\theta(x;q) - \theta(y;q)\right) - \left(\theta(x;r) - \theta(y;r)\right) = \sum_i \sum_j \left[\frac{\partial^2 \theta(z^i;s)}{\partial q_i \partial x_j}\right](x_j - y_j)(q_i - r_i). $$ If all cross partial derivatives are positive, then the right hand side is also positive if $x \ge y$ and $q \ge r$. As such, $$ \theta(x;q) - \theta(y;q) \ge \theta(x;r) - \theta(y;r) $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.